Frustrated double and single ionization in a two-electron triatomic molecule H+3. (4th November 2016) - Chen, A; Lazarou, C; Price, H; Emmanouilidou, A
Abstract: Using a semi-classical model, we study the formation of highly excited neutral fragments during the fragmentation of H 3 +, a two-electron triatomic molecule, driven by an intense near-IR laser field. To do so, we first formulate a microcanonical distribution for arbitrary one-electron triatomic molecules. We then study frustrated double and single ionization in strongly driven H 3 + and compute the kinetic energy release of the nuclei for these two processes. Moreover, we investigate the dependence of frustrated ionization on the strength of the laser field as well as on the geometry of the initial molecular state.